Miserable and Cruel – Construction of the Image of a Woman and Femininity by Users of the Hashtag “Loser” on the Wykop.pl Portal - Załęska, Olga (Konteksty Społeczne, 2024)
The article is based on an analysis of content posted by selected users of the Wykop.pl website under the hashtag “loser”. This hashtag gathers young heterosexual men who consider themselves unfi t for society and losers in life. The biggest source of their frustration is the non-existence of their sex life – they cannot fi nd female partners for sexual or romantic relationships despite their clear desire to do so. The “losers” (as they call themselves) make the lack of a woman the main axis of their identity, therefore this text focuses on how her character is constructed and how she acts with the diff erent types (“alpha male”, “beta ATM”, “loser”) into which users divide men. The “losers” (as they call themselves) make the lack of a woman the main axis of their identity, therefore this text focuses on how her character is constructed and how she ranks against the diff erent types (“alpha male”, “beta ATM”, “loser”) into which users divide men. The analysis also focuses on the nature of the pseudo-biological language used on hashtags and how their narratives make visible their perceived repulsion towards women. Attention was also paid to issues of lower class membership in users’ statements, which may indicate that this membership is the source of the social movement of losers and their aspirations for conservative revolution. Ruth Wodak’s critical discourse analysis was the main tool used to conduct the analysis. Artykuł powstał na kanwie analizy treści zamieszczonych przez wybranych użytkowników serwisu Wykop.pl pod hasztagiem „przegryw”. Hasztag ten gromadzi młodych heteroseksualnych mężczyzn, którzy uważają się za nieprzystosowanych do oczekiwań społecznych oraz przegranych życiowo. Największym źródłem ich frustracji jest absencja życia seksualnego – nie mogą oni znaleźć partnerek do relacji seksualnych ani romantycznych mimo wyraźnych chęci. „Przegrywi” (jak sami siebie nazywają) czynią główną osią swojej tożsamości brak relacji z kobietą, dlatego też niniejszy tekst koncentruje się na tym, w jaki ...